Vehicle wiper blades

By adding specific compositions to the polyurethane material of the vehicle wiper blade, the aggregation of the hard chain segments is suppressed, and the fineness and uniform dispersion of the hard chain segments are achieved, and the existing vehicle wiper blades are insufficiently wiping on the glass surface is solved, and excellent wiping properties and contact force uniformity are achieved.

CN116057096BActive Publication Date: 2025-02-28CANON KK
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202180058811.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-07-07
Filing Date
2021-07-30
Publication Date
2025-02-28
Estimated Expiration
2041-07-30

AI Technical Summary

Technical Problem

The existing vehicle wiper blades have insufficient wiping properties on the glass surface, resulting in uneven contact, causing tremor and unhappiness, and may reduce the wiping properties.

Method used

Using a polyurethane material containing a specific composition, the isocyanate compound of diisocyanate and trifunctional or above polyfunctional isocyanate, as well as a polyfunctional or above polyfunctional alcohol, is used to inhibit the aggregation of the hard segments, thereby achieving microscopic refinement and uniform dispersion of the hard segments.

Benefits of technology

Excellent wipeability of the wiper blade for vehicle is achieved, stripe-like wiping residues are avoided, and contact force uniformity of the surface of the cleaning member is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116057096B_ABST
    Figure CN116057096B_ABST
Patent Text Reader

Abstract

A vehicle wiper blade having excellent wiping performance is provided. A vehicle wiper blade, wherein a portion of a lip of the wiper blade is brought into contact with a surface of a component to be cleaned, wherein: the polyurethane in the lip contains a reaction product of a composition comprising: an isocyanate compound containing a diisocyanate and a trifunctional or higher polyfunctional isocyanate, and an alcohol containing a trifunctional or higher polyfunctional alcohol; the diisocyanate has an aromatic ring in its molecule; M2 / M1 is 0.001-0.028, M3 / M1 is 0.020-0.110, and M2 / M3 is 0.013-0.300, wherein M1 is the detected amount of all ions, M2 is a trifunctional or higher polyfunctional isocyanate, and M3 is a diisocyanate; and the concentration of the trifunctional or higher polyfunctional alcohol in the polyurethane is 0.12-0.65 mmol / g.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a vehicle wiper blade for wiping a surface of a member to be cleaned. Background Art

[0002] For a wiper blade for a vehicle, natural rubber or chloroprene rubber, etc. is used. Rubber has an unsaturated bond and is therefore easily deteriorated. As one of the prior arts, PTL 1 proposes using polyurethane as a material having no unsaturated bond.

[0003] Citation List

[0004] Patent Literature

[0005] [PTL1] Japanese Patent Publication No. 2004-51894 Summary of the invention

[0006] Problem that the invention aims to solve

[0007] In recent years, in order to ensure a good field of vision, the glass surface is often treated with water-repellent treatment or wax coating. As a result, although the local wiping performance is improved, uneven contact with the glass surface occurs, which may cause vibration. The abnormal noise caused by the uneven contact brings discomfort to the driver. In addition, the vibration itself may cause a reduction in wiping performance. According to the research conducted by the inventors, the wiper blade made of polyurethane as described in PTL 1 still has room for improvement in the wiping performance of attachments such as raindrops attached to the windshield. One aspect of the present disclosure is to provide a wiper blade for a vehicle that can exert excellent wiping performance.

[0008] Solutions for solving problems

[0009] According to one aspect of the present disclosure, there is provided

[0010] A vehicle wiper blade, comprising:

[0011] a scraper blade support; and

[0012] A lip portion pivotably connected to the scraper support portion via a neck portion,

[0013] A portion of the lip is brought into contact with the surface of the member to be cleaned, thereby cleaning the surface of the member to be cleaned,

[0014] The lips contain polyurethane,

[0015] The polyurethane comprises reactants of a composition comprising:

[0016] an isocyanate compound comprising a diisocyanate and a trifunctional or higher polyfunctional isocyanate, and

[0017] Alcohols including trifunctional or higher polyfunctional alcohols,

[0018] The diisocyanate has an aromatic ring in the molecule, wherein

[0019] When polyurethane is heated to 1000°C at a heating rate of 10°C / s using a direct sample introduction type mass spectrometer that heats and vaporizes the sample in an ionization chamber and ionizes the sample molecules, the amount of all ions detected is defined as M1.

[0020] The integrated intensity of the peak in the extracted ion thermogram corresponding to the range of m / z values ​​derived from trifunctional or higher polyfunctional isocyanates is defined as M2, and

[0021] The integrated intensity of the peak in the extracted ion thermogram corresponding to the range of m / z values ​​derived from diisocyanate is defined as M3,

[0022] M2 / M1 is 0.001~0.028,

[0023] M3 / M1 is 0.020~0.110,

[0024] M2 / M3 is 0.013 to 0.300, and

[0025] The concentration of the trifunctional or higher polyfunctional alcohol in the polyurethane is 0.12 mmol / g to 0.65 mmol / g.

[0026] Effects of the Invention

[0027] One aspect of the present disclosure can provide a vehicle wiper blade capable of exhibiting excellent wiping performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] [ Figure 1 ]An example of a schematic diagram of a wiper blade.

[0029] [ Figure 2 ] Figure 2 (a) and Figure 2 (b) are each an explanatory diagram showing a state of a wiper blade during a cleaning process.

[0030] [ Figure 3 ]Enlarged view near the first edge.

[0031] [ Figure 4 ]Enlarged view near the first line segment.

[0032] [ Figure 5 ] Figure 5 (a) and Figure 5 (b) shows the binarized images of Example 1 and Comparative Example 1, respectively. DETAILED DESCRIPTION

[0033] In the present disclosure, unless otherwise specified, the description of "XX or more and YY or less" or "XX to YY" expressing a numerical range means a numerical range including the lower limit and the upper limit as endpoints.

[0034] When a numerical range is described in sections, the upper and lower limits of each numerical range can be arbitrarily combined.

[0035] The present inventors believe that when using a conventional polyurethane wiper blade, the difference in the way the hard segment and the soft segment in the polyurethane transmit force to the surface to be cleaned causes, for example, streaky wiping residues to appear.

[0036] Further research based on such considerations has found that it is effective to further improve the wiping property by including a specific polyurethane in the elastic portion of the wiper blade. The specific polyurethane inhibits the aggregation of the hard segments. As a result, it is conceivable that the transmission of force to the cleaned surface becomes uniform along the longitudinal (width) direction of the wiper blade, and the occurrence of streaky wiping residues can be effectively inhibited.

[0037] <Construction of vehicle wiper blade>

[0038] The vehicle wiper blade (hereinafter also simply referred to as the wiper blade) according to the present disclosure can be used for equipment including vehicles represented by automobiles, transportation equipment such as airplanes or ships, or industrial machinery equipment such as construction machinery.

[0039] like Figure 1 As shown in FIG. 1 , the wiper blade includes a blade support portion 1 and a lip portion 3 swingably connected to the blade support portion via a neck portion 2. The wiper blade is formed to have substantially the same cross-sectional shape along the length direction.

[0040] Although the shape of the lip 3 is not particularly limited, for example, the shape may be such that the width of the cross section in a direction perpendicular to the longitudinal direction of the wiper blade gradually decreases from the side close to the blade support portion 1 toward the direction away from the blade support portion 1.

[0041] The wiper blade contacts the surface of a member to be cleaned, such as a glass surface, with a part of its lip portion, thereby cleaning the surface of the member to be cleaned.

[0042] For example, the following aspect may be mentioned: in a cross section along a direction orthogonal to the length direction of the wiper blade, the width of the neck portion 2 is narrow relative to the blade support portion 1 and the lip portion 3 .

[0043] Results, such as Figure 2 As shown in FIG. 1 , the lip 3 is inclined in the wiping direction and contacts the surface of the member to be cleaned.

[0044] Figure 2 In Figure 2 (a) and Figure 2 (b) are each an explanatory diagram showing a state of a wiper blade during cleaning.

[0045] R represents the cleaning direction of the wiper blade. It indicates that the surface to be in contact with the component to be cleaned is switched according to the cleaning direction.

[0046] For example, in Figure 2 In (a), the movement of the neck 2 causes the lip 3 of the wiper blade to tilt toward the right side of the paper surface, so that the right side of the lip 3 on the paper surface abuts against the member 10 to be cleaned.

[0047] On the other hand, Figure 2 In (b), the movement of the neck 2 causes the lip 3 of the wiper blade to tilt toward the left side of the paper surface, so that the left side of the lip 3 on the paper surface abuts against the member 10 to be cleaned.

[0048] In this way, from along Figure 2 (a) The sweep direction of the arrow R is along Figure 2 The switching of cleaning in the direction of arrow R in (b) switches the surface to be in contact with the member to be cleaned from the right side of the lip 3 in the paper to the left side in the paper.

[0049] As described above, it is considered that in conventional polyurethane wiper blades, streaky wiping residues occur due to differences in the way that force is transmitted to the member to be cleaned between the hard segment and the soft segment in the polyurethane.

[0050] The reason is presumed to be as follows. It is believed that for the polyurethane used for the conventional wiper blade, the hard segments are aggregated so that the hard segments are aggregated in a block shape. As a result, at the microscopic polymer level, a state occurs in which a significant difference in hardness between the hard segments and the soft segments occurs, that is, a state in which hardness is uneven exists.

[0051] It is considered that when the wiper blade is brought into contact with the member to be cleaned in this state, portions with strong contact force and portions with weak contact force appear irregularly; therefore, during cleaning (wiping operation), streaky wiped residues appear.

[0052] Therefore, it is believed that the hardness unevenness can be eliminated by making the hard segments in the polyurethane fine and evenly dispersed. Based on this consideration, the composition of the polyurethane is set to specific conditions. This allows the hard segments in the polyurethane to be fine and evenly dispersed. As a result, the wiping property of the component to be cleaned can be further improved.

[0053] The lip of the present disclosure comprises polyurethane,

[0054] The polyurethane comprises reactants of a composition including an isocyanate compound including a diisocyanate and a tri- or higher-functional polyfunctional isocyanate, and an alcohol including a tri- or higher-functional polyfunctional alcohol.

[0055] This diisocyanate has an aromatic ring in the molecule.

[0056] Furthermore, when polyurethane is heated to 1000°C at a heating rate of 10°C / s using a direct sample introduction type mass spectrometer that heats and vaporizes the sample in an ionization chamber and ionizes the molecules of the sample, the amount of all ions detected is defined as M1.

[0057] The integrated intensity of the peak in the extracted ion thermogram corresponding to the range of m / z values ​​derived from trifunctional or higher polyfunctional isocyanates is defined as M2, and

[0058] The integrated intensity of the peak in the extracted ion thermogram corresponding to the range of m / z values ​​derived from diisocyanate is defined as M3,

[0059] M2 / M1 is 0.001~0.028,

[0060] M3 / M1 is 0.020~0.110,

[0061] M2 / M3 is 0.013 to 0.300, and

[0062] The concentration of the trifunctional or higher polyfunctional alcohol in the polyurethane is 0.12 mmol / g to 0.65 mmol / g.

[0063] A detailed description will be given below.

[0064] The hard segments are mainly formed by aggregation caused by the interaction between the urethane bonds of diisocyanates or the interaction between aromatic rings. The hard segments tend to become larger when they can overlap each other regularly. Therefore, by disrupting the regularity, the miniaturization of the hard segments can be achieved.

[0065] Therefore, as described above, by achieving a composition containing trifunctional or higher polyfunctional isocyanates and trifunctional or higher polyfunctional alcohols in an appropriate concentration range, orientation is suppressed by steric hindrance. As a result, the hard segments become less likely to aggregate. Therefore, the hard segments are miniaturized and uniformly dispersed.

[0066] As a result, the contact force of the abutment portion with the cleaned member is uniformed in the entire area along the length direction of the lip. Therefore, the contact portion can be uniformly movable on the surface of the cleaned member. Therefore, in the entire area along the length direction of the wiper blade, excellent wiping performance can be exerted without causing uneven wiping.

[0067] When M2 / M1 is 0.001 or more, a structure derived from trifunctional or higher-functional isocyanate having low crystallinity is introduced into the polyisocyanate forming the hard segment, which can suppress aggregation of the hard segment. This can make the hard segment finely and uniformly dispersed.

[0068] When M2 / M1 is 0.028 or less, aggregation between low molecular weight multifunctional components can be suppressed, which can suppress aggregation of hard segments. In the case of 0.015 or less, aggregation can be suppressed at a higher level.

[0069] When M3 / M1 is 0.020 or more, the molecular weight tends to be increased during the curing reaction, thereby improving the wear resistance.

[0070] Since the higher the concentration of diisocyanate, the more aggregation of hard segments tends to proceed, M3 / M1 is 0.110 or less. By setting M3 / M1 to 0.110 or less, aggregation of hard segments can be further suppressed. In addition, 0.100 or less is preferred.

[0071] When M2 / M3 is 0.013 or more, sufficient trifunctional or higher-functional isocyanate exists relative to diisocyanate, so that crystallization caused by diisocyanate is suppressed. This can suppress aggregation of hard segments.

[0072] On the other hand, when M2 / M3 is 0.300 or less, aggregation between low molecular weight multifunctional components can be suppressed, which can suppress aggregation of hard segments. In the case of 0.150 or less, aggregation can be suppressed at a higher level.

[0073] Furthermore, it is preferred that

[0074] M2 / M1 is 0.001~0.015,

[0075] M3 / M1 is 0.040~0.100, and

[0076] M2 / M3 is 0.013 to 0.150, and

[0077] The concentration of the trifunctional or higher polyfunctional alcohol in the polyurethane is 0.22 mmol / g to 0.39 mmol / g.

[0078] The concentration of trifunctional or higher polyfunctional alcohol in polyurethane is calculated by the following formula (1). When the concentration of trifunctional or higher polyfunctional alcohol falls within the above range, the inhibitory effect of hard segment aggregation is high. That is, the concentration of trifunctional or higher polyfunctional alcohol in polyurethane is 0.12 mmol / g to 0.65 mmol / g, and preferably 0.22 mmol / g to 0.39 mmol / g.

[0079] Formula (1): Concentration of trifunctional or higher polyfunctional alcohol (mmol / g) =

[0080] [Amount of trifunctional or higher polyfunctional alcohol (g) / molecular weight of trifunctional or higher polyfunctional alcohol × 1000] / [mass of polyurethane (g)]

[0081] The polyurethane is preferably a polyurethane elastomer.

[0082] The polyurethane elastomer can be obtained from raw materials mainly including polyol, chain extender, polyisocyanate, catalyst and other additives.

[0083] Polyurethane elastomers are block copolymers comprising hard segments and soft segments. The hard segments are usually composed of polyisocyanates and chain extenders containing short-chain diols. On the other hand, the soft segments are usually composed of long-chain polyols such as polyester polyols, polyether polyols, polycarbonate polyols, and polyisocyanates.

[0084] As the polyisocyanate, a diisocyanate and a trifunctional or higher-functional polyisocyanate are used in combination.

[0085] Examples of the diisocyanate may include the following.

[0086] 4,4'-diphenylmethane diisocyanate (4,4'-MDI), 2,4-toluene diisocyanate (2,4-TDI), 2,6-toluene diisocyanate (2,6-TDI), xylene diisocyanate (XDI), 1,5-naphthalene diisocyanate (1,5-NDI), p-phenylene diisocyanate (PPDI), tetramethylxylene diisocyanate (TMXDI), and carbodiimide-modified MDI.

[0087] As the diisocyanate, a diisocyanate having an aromatic ring in the molecule is used. Use of a diisocyanate containing an aromatic ring can provide good mechanical properties and high reactivity.

[0088] The diisocyanate preferably has a structure in which NCO is directly bonded to an aromatic ring. As a result, aggregation of the hard segment can be further suppressed, and finer dispersion thereof can be achieved.

[0089] Examples of the trifunctional or higher polyfunctional isocyanate may include the following.

[0090] Polymeric MDI, triphenylmethane-4,4',4"-triisocyanate (TTI), tri(phenylisocyanate)phosphorothioate (TPTI), 4-isocyanatemethyl-1,8-octamethylene diisocyanate, 1,3,6-hexamethylene triisocyanate, trimethylbenzene triisocyanate, diphenylmethane-2,4-4'-triisocyanate.

[0091] The trifunctional or higher polyfunctional isocyanate is more preferably at least one selected from the group consisting of polymeric MDI, triphenylmethane-4,4′,4″-triisocyanate, and tris(phenylisocyanate)phosphorothioate.

[0092] The polyfunctional isocyanate of trifunctional or higher is preferably at least one selected from the group consisting of polymeric MDI and tri(phenyl isocyanate)phosphorothioate. The isocyanate has a methylene or ether bond between NCO. Therefore, the distance between the carbamate bonds can be appropriately maintained. Therefore, this is preferred for suppressing the aggregation of the hard segment.

[0093] Polymeric MDI is represented by the following chemical formula (1) and chemical formula (1)'.

[0094] In the chemical formula (1)', n is preferably 1 or more and 4 or less.

[0095] Chemical formula (1) represents the case where n is 1 in Chemical formula (1)'.

[0096]

[0097] Branching by trifunctional or higher polyfunctional alcohols can suppress crystallization and aggregation of hard segments.

[0098] On the other hand, when there are too many branches, the density of urethane bonds around the trifunctional or higher polyfunctional alcohol increases, so that the hard segments tend to become more likely to aggregate. Therefore, among the trifunctional or higher polyfunctional alcohols, trifunctional alcohols are preferably used.

[0099] Among them, alcohols represented by the following formula (a) or (b) are preferred because they have a methylene group adjacent to a hydroxyl group, which allows the distance between urethane bonds to be appropriately maintained.

[0100] Specific examples of trifunctional or higher polyfunctional alcohols may include trimethylolethane (a type in which R1 in the following formula (a) is CH3), trimethylolpropane (TMP: a type in which R1 in the following formula (a) is C2H5), glycerol, pentaerythritol, and sorbitol.

[0101] The trifunctional or higher polyfunctional alcohol is preferably at least one selected from the group consisting of alcohols represented by the following formulae (a) and (b), glycerol, and pentaerythritol.

[0102] Tri- or higher-functional polyfunctional alcohols may be used alone or in combination of two or more thereof.

[0103]

[0104] In formulae (a) and (b), R1 and R2 each independently represent H, CH3 or C2H5.

[0105] Examples of the polyol may include the following.

[0106] Polyester polyols such as polyethylene adipate polyester polyol, polybutylene adipate polyester polyol, polyhexane adipate polyester polyol, (polyethylene / polypropylene) adipate polyester polyol, (polyethylene / polybutylene) adipate polyester polyol, and (polyethylene / polyneopentene) adipate polyester polyol; polycaprolactone-based polyols obtained by ring-opening polymerization of caprolactone; polyether polyols such as polyethylene glycol, polypropylene glycol, and polytetramethylene glycol; and polycarbonate diols. These may be used alone or in combination of two or more thereof.

[0107] Among the above-mentioned polyols, polyester polyol using an adipate ester is preferable because a polyurethane elastomer excellent in mechanical characteristics can be obtained.

[0108] In particular, polyols such as polybutylene adipate polyester polyol or polyhexylene adipate polyester polyol having an alkylene group having more than 4 carbon atoms are preferred. In addition, polyols such as polybutylene adipate polyester polyol and polyhexylene adipate polyester polyol having different carbon atoms are preferably used in combination. Using different types of polyols can also improve the crystallization suppression of the soft segment so that the soft segment becomes less likely to aggregate. As a result, the dispersibility of the hard segment can be further improved.

[0109] As the chain extender, diols and trifunctional or higher-functional alcohols that can extend the chain of the polyurethane elastomer can be used.

[0110] Examples of the diol may include the following.

[0111] Ethylene glycol (EG), diethylene glycol (DEG), propylene glycol (PG), dipropylene glycol (DPG), 1,4-butanediol (1,4-BD), 1,6-hexanediol (1,6-HD), 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, xylylene glycol (p-phenylenediol), and triethylene glycol. These may be used alone or in combination of two or more thereof.

[0112] As the catalyst, a commonly used catalyst for curing polyurethane elastomers can be used. Examples thereof may include tertiary amine catalysts. Specific examples thereof may include the following. Amino alcohols such as dimethylethanolamine, N,N,N'-trimethylaminopropylethanolamine and N,N'-dimethylhexanolamine; trialkylamines such as triethylamine; tetraalkyldiamines such as N,N,N'N'-tetramethyl-1,3-butanediamine; and triethylenediamine, piperazine compounds and triazine compounds. In addition, organic acid salts of alkali metals such as potassium acetate or potassium octoate may also be used.

[0113] Furthermore, metal catalysts generally used for urethanization such as dibutyltin dilaurate may also be used. These may be used alone or in combination of two or more thereof.

[0114] Additives such as a pigment, a plasticizer, a water-repellent agent, an antioxidant, an ultraviolet absorber, and a light stabilizer may be mixed into the raw materials constituting the lip as necessary.

[0115] <Manufacturing method of wiper blade>

[0116] The manufacturing method of the wiper blade is not particularly limited and can be selected from known methods.

[0117] For example, a polyurethane elastomer raw material composition is injected into a cavity of a wiper blade mold, and heated and cured. As a result, a lip portion can be obtained.

[0118] Optionally, the front end of the lip may be cut to form a shape. By doing so, the contact surface of the lip with the member to be cleaned can be formed with high smoothness.

[0119] Still alternatively, it is also acceptable to manufacture a wiper blade by manufacturing a pair of molded bodies in a tandem shape formed in such a manner that the lips abut against each other while opposing each other, and cutting in the length direction.

[0120] <Full process including wiper arm>

[0121] The wiper blade disclosed herein can be used in various types of wiper devices such as tandem type and opposing wiping type.

[0122] [Example]

[0123] Hereinafter, the disclosure will be described by way of manufacturing examples, embodiments and comparative examples. However, the disclosure is not limited to embodiments etc. at all. For other raw materials other than the raw materials shown in the embodiments and comparative examples, reagents or industrial chemicals are used. In addition, unless otherwise stated, all "parts" in the embodiments and comparative examples are based on mass.

[0124] [Example 1]

[0125] The materials in the following Table 1 were mixed and reacted with each other at a temperature of 80° C. for 3 hours, thereby preparing a prepolymer having an NCO content of 10.6% by mass.

[0126] [Table 1]

[0127]

[0128] The materials described in the following Table 2 were mixed to prepare a curing agent.

[0129] [Table 2]

[0130]

[0131] The above prepolymer and the above curing agent are mixed to prepare a raw material composition of polyurethane. The raw material composition is injected into the cavity of the molding die for the vehicle wiper blade and cured at a temperature of 130° C. for 2 minutes. Then, demolding is performed, and a polyurethane molded body is obtained. In addition, a release agent A is applied to the cavity of the molding die before the raw material composition is injected. The release agent A is a mixture of the materials shown in Table 3 below.

[0132] [Table 3]

[0133]

[0134] The lip front end side of the obtained polyurethane molded body was cut off, and the wiper blade according to the present embodiment was obtained. The thickness of the lip front end was set at 0.6 mm, and the length in the longitudinal direction was set at 450 mm. The wiper blade thus obtained was evaluated as follows.

[0135] [Evaluation 1: Measurement of hard segment size]

[0136] The size of the hard segment is measured using a scanning probe microscope (SPM) (trade name: MFP-3D-Origin, manufactured by Oxford Instruments Co.) in the following manner.

[0137] The sample preparation method and the like are as follows.

[0138] In this article, Figure 2 (a) and Figure 2 As shown in FIG. 2 , the lip portion 3 of the vehicle wiper blade has a first tapered surface 5 that is to abut against the member 10 to be cleaned and constitutes the tapered portion 4, a second tapered surface 6 on the opposite side of the first tapered surface 5, and a front end surface 7, wherein the front end surface 7, together with the first tapered surface 5 and the second tapered surface 6, constitutes a first edge 8 and a second edge 9 on the side of the lip portion 3 that is farthest from the blade support portion 1 (for the first edge, the second edge and the front end surface, see FIG. 2 ). Figure 1 and Figure 3 ).

[0139] The inventors observed the reciprocating behavior of the wiper blade during cleaning. As a result, it was confirmed that during cleaning, the wiper blade opposite to the cleaned member contacts the cleaned member at the first tapered surface and the second tapered surface included in the lip portion, in an area centered at positions approximately 10 μm away from the first edge and the second edge, respectively.

[0140] Therefore, if Figure 3 and Figure 4As shown in , when assuming that a first line segment 11 with a distance of 10 μm from the first edge and a length of L1 is drawn parallel to the first edge on the first conical surface of the obtained wiper blade, three 2 mm square measurement samples with points P0, P1 and P2 at (1 / 8) L1, (1 / 2) L1 and (7 / 8) L1 from one end side on the first line segment as the center of gravity and one side parallel to the first line segment are cut out. Then, using a cryo-microtome (UC-6 (trade name), manufactured by Leica Microsystems Co.), polyurethane sheets with P0, P1 or P2 as the center of gravity, one side parallel to the first line segment, each 100 μm square and each 1 μm thick are cut out from each measurement sample at -50°C. In this way, three measurement samples are prepared. Each obtained measurement sample is placed on a smooth silicon wafer and allowed to stand for 24 hours at a room temperature of 25°C and a humidity of 50%.

[0141] Then, the silicon wafer with the measurement sample on it was placed on the SPM stage, and its SPM observation was performed. In addition, the spring constant and proportional constant of the silicon cantilever (trade name: OMCL-AC160, manufactured by Olympus Corporation, tip curvature radius: 8nm) were confirmed in advance by the thermal noise method equipped with this SPM device as follows (spring constant: 30.22nN / nm, proportional constant: 82.59nm / V).

[0142] Furthermore, the cantilever is tuned in advance, thereby obtaining the resonant frequency (285 kHz (first order) and 1.60 MHz (higher order)) of the cantilever.

[0143] The measurement mode of SPM was set to AM-FM mode, the free amplitude of the cantilever was set to 3 V (first order) and 25 mV (high order), and the set point amplitude was set to 2 V (first order). In a 1 μm×1 μm square field of view, scanning was performed under the conditions of a scanning speed of 1 Hz and 256 scanning points in the vertical direction and 256 in the horizontal direction, thereby acquiring three phase images (256 grayscales). In addition, for the field of view, the position was selected so that P0, P1, and P2 of each measurement sample existed in the center of the field of view, and one side was parallel to the first line segment.

[0144] Each obtained phase image was subjected to binarization processing using an image processing analysis system (trade name: Luzex-AP, manufactured by NIRECO Corporation). Specifically, the phase image was binarized using the binarization setting function of the image processing analysis system. In addition, the threshold in the binarization setting function was set at 85 (the 85th order in 256 orders). This operation provides a binarized image in which the soft segment is displayed in black and the hard segment is displayed in white. As an example, Figure 5(a) shows the binarized image of Example 1, and Figure 5 (b) shows the binarized image of Comparative Example 1.

[0145] The size of the hard segment in the obtained binary image is measured using an image processing analysis system. The size of the hard segment is measured using the "equivalent circle diameter" parameter.

[0146] In addition, for the second conical surface, three binary images are prepared in the same manner as for the first conical surface. The size of the hard segment in each binary image is measured. The arithmetic mean of the sizes of all hard segments measured from the total of six binary images thus obtained is defined as the size of the hard segment in the present disclosure.

[0147] [Evaluation 2: Measurement of M1, M2 and M3]

[0148] The measurement of M1 to M3 was performed using a direct sample introduction method (DI method) in which the sample is introduced directly into an ion source without passing through a gas chromatograph (GC). As an apparatus, an ion trap type GC / MS (trade name: POLARIS Q, manufactured by Thermo Fisher Scientific Co.) was used. As a direct introduction probe, a direct exposure probe (DEP) was used.

[0149] 0.1 μg of sample was measured at each point P0, P1, and P2 of the first and second conical surfaces described in Evaluation 1 in the following manner. That is, each collected sample was fixed at the filament located at the front end of the probe and directly inserted into the ionization chamber. Subsequently, the sample was rapidly heated from room temperature to 1000°C at a constant heating rate (10°C / s), and the vaporized gas was detected by means of a mass spectrometer.

[0150] When the total ion detection amount M1 is assumed to be the sum of the integrated intensities of all peaks in the obtained total ion current thermogram, the sum of the integrated intensities of the peaks of the extracted ion thermogram of the m / z values ​​derived from trifunctional or higher polyfunctional isocyanates is assumed to be M2, and the integrated intensity of the peaks of the extracted ion thermogram corresponding to the range of m / z values ​​derived from diisocyanates is assumed to be M3, the values ​​of M1, M2 and M3 are used to calculate (M2 / M1), (M3 / M1) and (M2 / M3). Then, the arithmetic mean of all the measured values ​​obtained from each sample of P0, P1 and P2 of the first conical surface and the second conical surface is referred to as (M2 / M1), (M3 / M1) and (M2 / M3) in the present disclosure.

[0151] Here, in this embodiment, for the elastic part of the polyurethane synthesized using polymerized MDI as a trifunctional or higher polyfunctional isocyanate, a peak of a cationized product derived from polymerized MDI was detected in the extracted ion thermogram obtained by the above analysis, and the peak had a peak top at each position where the m / z value representing n=1 in the structure represented by the chemical formula (1)' is in the range of 380.5 to 381.5, the m / z value representing n=2 is in the range of 511.5 to 512.5, the m / z value representing n=3 is in the range of 642.5 to 643.5, and the m / z value representing n=4 is in the range of 773.5 to 774.5. Therefore, in this embodiment, the sum of the integrated intensities of the peaks is referred to as M2.

[0152] In addition, in other examples described later, TTI used as a trifunctional or higher polyfunctional isocyanate has a structure shown in the following chemical formula (2). Then, for the elastic part containing the polyurethane synthesized using TTI, a peak derived from a cationized product of TTI was detected in the extracted ion thermogram obtained by the above analysis, and the peak had a peak top in the range of m / z 366.5 to 367.5. Therefore, in this example, the integrated intensity of this peak is referred to as M2.

[0153]

[0154] Similarly, in the examples described later, TPTI used as a trifunctional or higher polyfunctional isocyanate has a structure represented by the following chemical formula (3). Then, for the elastic portion comprising the polyurethane synthesized using TPTI, a peak derived from a cationized product of TPTI was detected in the extracted ion thermogram obtained by the above analysis, and the peak had a peak top in the range of m / z 464.5 to 465.5. Therefore, in this example, the integrated intensity of this peak is referred to as M2.

[0155]

[0156] On the other hand, 4,4'-MDI used as diisocyanate in this example has a structure represented by the following chemical formula (7). For the elastic part including the polyurethane synthesized using 4,4'-MDI, a peak derived from a cationized product of 4,4'-MDI was detected in the extracted ion thermogram obtained by the above analysis, and the peak had a peak top at a position of m / z of 249.5 to 250.5. Therefore, the integrated intensity of this peak is referred to as M3.

[0157]

[0158] Toluene diisocyanate (TDI) used as diisocyanate in other examples has structures represented by the following chemical formulas (4a) and (4b).

[0159] For the elastic part including polyurethane synthesized using TDI, a peak derived from a cationized product of TDI was detected in the extracted ion thermogram obtained by the above analysis, and the peak had a peak top in the range of m / z 173.5 to 174.5. Therefore, the integrated intensity of this peak is referred to as M3.

[0160]

[0161] Metaphenylene diisocyanate (XDI) as a diisocyanate has a structure represented by the following chemical formula (5). For the elastic part including the polyurethane synthesized using XDI, a peak derived from a cationized product of XDI was detected in the extracted ion thermogram obtained by the above analysis, and the peak had a peak top in the range of m / z 187.5 to 188.5. Therefore, the integral value of this peak is referred to as M3.

[0162]

[0163] In addition, 1,5-naphthalene diisocyanate (NDI) as a diisocyanate has a structure represented by the following chemical formula (6). For the elastic part including the polyurethane synthesized using NDI, a peak derived from a cationized product of NDI was detected in the extracted ion thermogram obtained by the above analysis, and the peak had a peak top in the range of m / z of 209.5 to 210.5. Therefore, the integrated intensity of this peak is called M3.

[0164]

[0165] [Evaluation 3: Measurement of types and concentrations of polyfunctional alcohols]

[0166] The detection of polyfunctional alcohols was performed by pyrolysis GC / MS (gas chromatography and mass spectrometry). The measurement conditions are shown below.

[0167] Sampling position: The sample sampled at each of P0, P1, and P2 of the first tapered surface and the second tapered surface is measured in the following manner.

[0168] Device:

[0169] ●Pyrolysis device: Trade name: EGA / PY-3030D, manufactured by Frontier Laboratories Ltd.

[0170] Gas chromatography apparatus: TRACE1310 gas chromatograph, manufactured by Thermo Fisher Scientific Co.

[0171] Mass spectrometer: ISQLT, manufactured by Thermo Fisher Scientific Co.

[0172] ●Thermal decomposition temperature: 500℃

[0173] ●GC column: inner diameter 0.25mm×30m stainless steel capillary column

[0174] ●Stationary phase: 5% phenyl polydimethylsiloxane

[0175] ● Heating conditions: Keep at 50℃ for 3 minutes and increase the temperature to 300℃ at 8℃ / min

[0176] ●MS conditions: mass range m / z 10~650

[0177] ●Scanning speed: 1 second / scan

[0178] The polyfunctional alcohol species were qualitatively characterized by GC / MS. A calibration curve was formed by GC analysis of the qualitative polyfunctional alcohol species of known concentrations, and quantification was performed by GC peak area ratios. Then, the arithmetic mean of all the measured values ​​obtained from each sample at P0, P1, and P2 of the first and second conical surfaces was defined as the concentration of the polyfunctional alcohol in the present disclosure.

[0179] <Evaluation 4: Evaluation of wiping performance>

[0180] The wiping performance of the wiper blade was evaluated using a test device for the wiping performance test described in Japanese Industrial Standard (JIS) D5710:1998 (Automobile Parts - Wiper Arm and Wiper Blade). In this test, the wiper blade was installed and water was sprayed in a mist form on the glass surface of the member to be cleaned. Then, the wiping of water on the glass surface after the wiper blade reciprocated once was visually confirmed and evaluated according to the following criteria.

[0181] [Wipe conditions]

[0182] Load to be applied to wiper blade: 10N / m

[0183] Wiping reciprocating speed of the wiper blade: 50 times / min

[0184] [Evaluation criteria]

[0185] ■ Grade A: 1 or less thin line (wiping residue of very thin stripes with a width of 0.5 mm or less), and 0 thick lines (wiping residue of thin stripes with a width of 1 mm or less) and wide lines (wiping residue of stripes with a width of up to about 1 to 20 mm, including a collection of several thin lines and thick lines and film-like wiping residue)

[0186] ■Level B: 2 thin lines, and 0 thick and wide lines,

[0187] ■Grade C: 2 thin lines, 1 thick line and 0 wide lines

[0188] ■Level D: 3 thin lines, 1 thick line and 0 wide lines

[0189] ■ Grade E: 4 or more thin lines, 2 or more thick lines, or 1 or more wide lines

[0190] [Examples 2 to 48 and Comparative Examples 1 to 6]

[0191] A prepolymer and a curing agent were obtained in the same manner as in Example 1, except that the materials and amounts compounded were changed as shown in Table 4 or Table 5. The obtained wiper blade was evaluated in the same manner as in Example 1.

[0192] In addition to the materials shown in Example 1, the details of the materials used will be shown below.

[0193] Polybutylene adipate polyester polyol having a number average molecular weight of 1000 (trade name: NIPPOLAN 4009, manufactured by TOSOH CORPORATION Ltd.) (hereinafter referred to as PBA 1000)

[0194] Polyhexamethylene adipate polyester polyol having a number average molecular weight of 1000 (trade name: NIPPOLAN 164, manufactured by TOSOH CORPORATION Ltd.) (hereinafter referred to as PHA 1000)

[0195] Polyhexamethylene adipate polyester polyol having a number average molecular weight of 2600 (trade name: NIPPOLAN 136, manufactured by TOSOH CORPORATION Ltd.) (hereinafter referred to as PHA2600)

[0196] Poly(hexamethylene adipate) polyester polyol having a number average molecular weight of 4500 (trade name: HS2H-451A, manufactured by HOKOKU Corporation) (hereinafter referred to as PHA4500)

[0197] Polytetramethylene ether glycol having a number average molecular weight of 1000 (trade name: PTG-1000SN, manufactured by Hodogaya Chemical Co., Ltd.) (hereinafter referred to as PTMG 1000)

[0198] Polytetramethylene ether glycol having a number average molecular weight of 2000 (trade name: PTG-2000SN, manufactured by Hodogaya Chemical Co., Ltd. (hereinafter referred to as PTMG 2000)

[0199] Glycerin (manufactured by Tokyo Chemical Industry Co., Ltd.)

[0200] Pentaerythritol (manufactured by Tokyo Chemical Industry Co., Ltd.)

[0201] Toluene diisocyanate (trade name: CORONATE T-80, manufactured by TOSOH CORPORATION Ltd.) (hereinafter referred to as TDI)

[0202] Metaphenylene diisocyanate (product code: D0127, manufactured by Tokyo Chemical Industry Co., Ltd.) (hereinafter referred to as XDI)

[0203] 1,5-Naphthalene diisocyanate (Product code: N0168, manufactured by Tokyo Chemical Industry Co., Ltd.) (hereinafter referred to as NDI)

[0204] Triphenylmethane-4,4',4"-triisocyanate (trade name: ULTIGHT SUPER CA, manufactured by Toho Kasei Kogyo Co., Ltd.) as a trifunctional or higher polyfunctional isocyanate (hereinafter referred to as TTI)

[0205] Tris(phenyl isocyanate) thiophosphoric acid as a trifunctional or higher polyfunctional isocyanate (trade name: ULTIGHT SUPER CAII, manufactured by Toho Kasei Kogyo Co., Ltd.) (hereinafter referred to as TPTI)

[0206] The evaluation results of Examples 1 to 48 and Comparative Examples 1 to 6 are shown in Tables 4 and 5.

[0207] [Table 4]

[0208]

[0209] [Table 5]

[0210]

[0211] The present disclosure is not limited to the above-described embodiments, and various modifications and changes may be made without departing from the spirit and scope of the present disclosure. Therefore, the following claims are intended to disclose the scope of the present disclosure.

[0212] This application claims priority based on Japanese Patent Application No. 2020-130696 filed on July 31, 2020 and Japanese Patent Application No. 2021-112683 filed on July 7, 2021, the entire contents of which are incorporated herein by reference.

[0213] Description of Reference Numerals

[0214] 1. Blade support

[0215] 2 Neck

[0216] 3. Lips

[0217] 4 Conical part

[0218] 5First conical surface

[0219] 6 Second conical surface

[0220] 7Front end

[0221] 8 First Edge

[0222] 9 The Second Edge

[0223] 10 Cleaned components

[0224] 11The first line segment

Claims

1. A vehicle wiper blade, characterized in that: It includes: A scraper blade supporting portion; and a lip portion pivotably connected to the scraper support portion via a neck portion, A portion of the lip is brought into contact with a surface of a member to be cleaned, thereby cleaning the surface of the member to be cleaned. The lip portion comprises polyurethane, The polyurethane comprises reactants of a composition comprising: an isocyanate compound comprising a diisocyanate and a trifunctional or higher polyfunctional isocyanate, and Alcohols including trifunctional or higher polyfunctional alcohols, The diisocyanate has an aromatic ring in the molecule, wherein When the polyurethane is heated to 1000°C at a heating rate of 10°C / s using a direct sample introduction type mass spectrometer that heats and vaporizes the sample in an ionization chamber and ionizes the molecules of the sample, the obtained The detected amount of all ions is defined as M1, The integrated intensity of the peak in the extracted ion thermogram corresponding to the range of m / z values ​​derived from trifunctional or higher polyfunctional isocyanates is defined as M2, and The integrated intensity of the peak in the extracted ion thermogram corresponding to the range of m / z values ​​derived from diisocyanate is defined as M3, M2 / M1 is 0.001~0.028, M3 / M1 is 0.020~0.110, M2 / M3 is 0.013 to 0.300, and The concentration of the trifunctional or higher polyfunctional alcohol in the polyurethane is 0.12 mmol / g to 0.65 mmol / g.

2. The vehicle wiper blade according to claim 1, wherein The M2 / M1 is 0.001 to 0.015, The M3 / M1 is 0.040 to 0.100, The M2 / M3 is 0.013 to 0.150, and The concentration of the trifunctional or higher polyfunctional alcohol in the polyurethane is 0.22 mmol / g to 0.39 mmol / g.

3. The vehicle wiper blade according to claim 1 or 2, The diisocyanate has a structure in which NCO is directly bonded to an aromatic ring.

4. The vehicle wiper blade according to claim 1 or 2, The trifunctional or higher polyfunctional isocyanate is at least one selected from the group consisting of polymeric MDI, triphenylmethane-4,4',4"-triisocyanate and tris(phenylisocyanate)phosphorothioate.

5. The vehicle wiper blade according to claim 1 or 2, The trifunctional or higher polyfunctional alcohol is at least one selected from the group consisting of an alcohol represented by the following formula (a), an alcohol represented by the following formula (b), and pentaerythritol: in, In the formulae (a) and (b), R1 and R2 each independently represent H, CH3 or C2H5.

Citation Information

Patent Citations

  • Wiper blade for vehicle

    JP2004051894A

  • Game machine

    JP2020130696A

  • Program, information processing device, and control method

    JP2021112683A

  • Method for producing cleaning blade

    CN104133359A

  • Cleaning blade

    CN108369394A